3D‐FE automatic procedure to evaluate the fatigue life extension by overloading. Issue 5 (8th January 2020) - Perdigão, Sandra; Cunha, Jorge; Nogueira, Filipe; Branco, Ricardo; Antunes, Fernando Ventura
Abstract: The present paper proposes a three‐dimensional numerical approach able to account for the effect of overloads on fatigue life extension in cracked geometries. The procedure starts with the analysis of the overload effects on plasticity induced crack closure via a three‐dimensional elastic‐plastic approach based on the node release technique. Then, the relationships between the crack opening values and the fatigue crack growth rates are introduced into the fatigue crack growth models, developed in the light of the adaptive remeshing concept, to estimate the fatigue lifetime.